A construção da imagem do colonizador na Revista Portugal colonial - Ferreira, Joana (elingUP: Revista Eletrónica de Linguística dos Estudantes da Universidade do Porto, 2018)
The main aim of this research paper is to analyze the linguistic mechanisms used by different addressers in the first number of the magazine Portugal Colonial in order to, not only give credibility to their own statements but also to regulate the beliefs, the attitudes and the behavior of the readers. Writing the present study allowed us to realize that the construction of the identity of the Portuguese colonizer is usually done by a process of enhancement of the latter, either through sentence structures and the use of lexicon aiming to praise him, or through a process of polarization against an external actant, in a conflict perspective. In addition, the linguistic material used to define the Self-presentation is notoriously more abundant than the linguistic material used to define the Other.